Undoing coups: The African Union and post-coup Intervention in Madagascar - Witt, Antonia (London (UK): Zed, 2022)
An in-depth analysis of international intervention in Madagascar following the 2009 coup, and what it means for African 'anti-coup' efforts.
Reordering what? Transition as executive politics -- Reordering with whom, for whom? Faking inclusivity -- Reordering how? Between pressure and evasion -- 6: Reproducing old, legitimating new orders -- Reordering Madagascar -- Reordering the international -- 7: Politics and power of post-coup interventions -- Madagascar in the bigger picture -- Implications -- So, what to do? -- Notes -- References -- List of interviews -- Index
Includes bibliographical references and index.
Keywords: African Union; z; Legitimacy of governments -- Africa; z; z; Peace studies & conflict resolution; Africa -- Politics and government -- 21st century; Afrique -- Politique et gouvernement